Indigenous Peoples’ Rights and Development Governance: Evaluating FPIC Compliance in Geothermal Power Development - Konfridus Roynaldus Buku; Victoria Dalima; Hendrikus Reinald Wawo (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2025)
Indigenous communities in Indonesia continue to experience rights violations linked to development projects that proceed without meaningful participation. In such contexts, the principle of Free, Prior, and Informed Consent (FPIC) is essential to ensure that Indigenous peoples can make voluntary decisions, receive timely information, and be recognized as legitimate decision-makers in their customary territories. This study examines FPIC implementation in the Mataloko Geothermal Power Plant (PLTP) project in Ngada Regency, East Nusa Tenggara, where project activities have been associated with social tension and conflict. The research aims to describe and analyse how FPIC has been applied in the Mataloko PLTP development process and how FPIC practices relate to community resistance. Using a concurrent triangulation mixed-methods design, this study combines a survey of 100 respondents from five villages with in-depth interviews, observation, and documentation review. Quantitative data were analysed descriptively and supported by statistical testing, while qualitative evidence was used to contextualize and explain community perceptions and conflict dynamics. Findings indicate that FPIC has not been implemented substantively. Communities reported limited freedom in decision-making, incomplete and uneven information disclosure, and consultation processes that did not sufficiently involve all affected groups or respect collective customary procedures. These deficiencies contributed to polarization within the community and strengthened resistance framed as demands for justice and protection of communal rights. This study contributes empirical evidence on FPIC gaps in geothermal development and underscores the practical importance of transparent, inclusive, and culturally grounded FPIC processes. Policy implications include early-stage consultation, open dissemination of impact information (including EIA findings), and safeguards to prevent rights-based conflict escalation.